EVALUATION OF SOME TPS PROGENIES AS TRANSPLANTED AND SEEDLING TUBER CROPS - Kumar, S.; Pandey, S. K.; Prasad, B (Potato Journal, 2013)
Eight TPS progenies along with controls, viz., TPS/C-3 and 92PT-27 were evaluated at Patna during 2002-05, for their yield potential as transplants and seedling tuber crops. Highest survival percentage of seedlings as well as total and marketable tuber yields were recorded in population JX-214 x TPS/D-150. This population also showed a high degree of resistance to late blight and tuber uniformity comparable with the controls. Thus, JX-214 x TPS/D-150 may be suitable for commercial cultivation in Bihar plains.